Callous-Unemotional Traits in Children and Adolescents: Psychometric properties of the portuguese version of the inventory of callous-unemotional traits - Carvalho, Marina (2018)
The Inventory of Callous and Unemotional Traits (ICU) was developed to measure callous-unemotional (CU) psychopathic traits in children and adolescents. Studies that have examined the factor structure of ICU showed considerable controversy. The aim of this study was to examine the factor structure and psychometric proprieties of the Portuguese translation of the ICU. A total of 1,011 children and adolescents (495 boys and 516 girls), mean age of 13.36 years, participated in this study. Exploratory factor analysis produced two factors: uncaring and callousness; Cronbach’s α for each of the factor was .83 and .79 for the total score. Significant main gender and interaction between gender and age effects were found; girls reported lower CU traits than boys; children reported higher CU traits compared to preadolescents and adolescents, particularly in boys. CU also correlated with emotional symptoms, conduct problems, and psychosocial impairment. Furthermore, CU traits related to conduct problems both in boys and in girls, although this relationship was higher for boys. To conclude, findings of the present study showed that the Portuguese version of the ICU seems to be a reliable and valid instrument to assess CU traits among children and adolescents in Portugal. However, the original 3-factor model was not supported.